Application of super-resolution and correlative double sampling in cryo-electron microscopy. (8th August 2022) - Sheng, Yuewen; Harrison, Peter J.; Vogirala, Vinod; Yang, Zhengyi; Strain-Damerell, Claire; Frosio, Thomas; Himes, Benjamin A.; Siebert, C. Alistair; Zhang, Peijun; Clare, Daniel K.
Abstract : A comparison of STA and SPA processed data acquired with/without super-resolution imaging mode enabled. Abstract : Developments in cryo-EM have allowed atomic or near-atomic resolution structure determination to become routine in single particle analysis (SPA). However, near-atomic resolution structures determined using cryo-electron tomography and sub-tomogram averaging (cryo-ET STA) are much less routine. In this paper, we show that collecting cryo-ET STA data using the same conditions as SPA, with both correlated double sampling (CDS) and the super-resolution mode, allowed apoferritin to be reconstructed out to the physical Nyquist frequency of the images. Even with just two tilt series, STA yields an apoferritin map at 2.9 Å resolution. These results highlight the exciting potential of cryo-ET STA in the future of protein structure determination. While processing SPA data recorded in super-resolution mode may yield structures surpassing the physical Nyquist limit, processing cryo-ET STA data in the super-resolution mode gave no additional resolution benefit. We further show that collecting SPA data in the super-resolution mode, with CDS activated, reduces the estimated B -factor, leading to a reduction in the number of particles required to reach a target resolution without compromising the data size on disk and the area imaged in SerialEM. However, collecting SPA data in CDS does reduce throughput, given that a similar resolution structure, with a slightly larger B -factor, is achievable with optimised parameters for speed in EPU (without CDS).